The 16th International Symposium &Amp;ldquo;Priorities of Chemistry for a Sustainable Development” PRIOCHEM 2020
DOI: 10.3390/proceedings2020057021
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Content, Antioxidant and Antimicrobial Activity of Hydrosols from Some Aromatic Lamiaceae Plants

Abstract: Hydrosols, also named hydrolates or aromatic waters, are considered distillation by-productsobtained during essential oil extraction from herbs or spices, which are usually discarded. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The hydrosol extract of Thymus capitatus L. rich in carvacrol effectively inhibited the growth of important fungal pathogens of Citrus sinensis L. including Aspergillus niger , Aspergillus oryzae , and Fusarium solani [ 238 ]. Gaspar-Pintiliescu et al [ 239 ] reported antibacterial activity for the aromatic water of Rosmarinus officinalis . Under in vitro conditions, strong nematicidal activity was associated with the use of hydrolates derived from Lavandula × intermedia Emeric ex Loisel.…”
Section: Aromatic Plants As Biocontrol Agentsmentioning
confidence: 99%
“…The hydrosol extract of Thymus capitatus L. rich in carvacrol effectively inhibited the growth of important fungal pathogens of Citrus sinensis L. including Aspergillus niger , Aspergillus oryzae , and Fusarium solani [ 238 ]. Gaspar-Pintiliescu et al [ 239 ] reported antibacterial activity for the aromatic water of Rosmarinus officinalis . Under in vitro conditions, strong nematicidal activity was associated with the use of hydrolates derived from Lavandula × intermedia Emeric ex Loisel.…”
Section: Aromatic Plants As Biocontrol Agentsmentioning
confidence: 99%